Online Marketing Strategy Optimization to Increase Sales and E-Commerce Development: An Integrated Approach in the Digital Age - Sanbella, Lunatari; Versie, Ikyboy Van; Audiah, Sipah (Pandawan Sejahtera Indonesia, 2024)
In the face of the challenges of intensifying competition in the rapidly growing world of e-commerce, this research focuses on investigating, identifying, and optimizing online marketing strategies to increase sales and support the growth of the e-commerce industry. This research aims to provide in-depth insights to online business owners by thoroughly understanding consumer behavior, technology trends, and digital market dynamics.This research adopts a mixed qualitative and quantitative approach by analyzing data from multiple sources. Customer surveys, sales data analysis, and case studies on successful e-commerce platforms provide the foundation for exploring consumer needs and preferences. Special emphasis is placed on assessing the sustainability of digital marketing strategies, utilization of social media, and implementation of the latest technologies in the e-commerce ecosystem.The research results are expected to provide comprehensive guidance for online marketing practitioners and e-commerce business owners. The findings not only include an in-depth understanding of consumer desires and market opportunities, but also provide valuable information on the effective use of social media, content strategies, and the latest ways to increase brand awareness, consumer engagement, and sales conversion. The use of technology is also emphasized as a key element in improving the competitiveness of e-commerce companies in the era of increasing digitalization.